2018
DOI: 10.21608/jappmu.2018.41163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Folic Acid Supplementation to Diets of Low Levels of Energy and Methionine of Developed Laying Hens in Summer Season on Performance, Physiological Status and Immune Response

Abstract: The objective of this study was to evaluate the effect of different levels of folic acid (FA) supplementation on productive and physiological performance and immune response of laying hens fed diets varying in methionine (M) and metabolizable energy (ME) levels. A total number of two hundred and sixteen of Silver Montazah laying hens (28 weeks old), were randomly divided into 12 treatment groups (18 hens / each). All birds were housed in individual cages. The experimental design was conducted in 2 x 2 x 3 fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…Also the daily protein intake (P≤0.05) and daily energy intake (P<0.01) of the former were significantly higher than those fed the H ME diet. Our results are in accordance with those of Nofal et al (2018), who demonstrated that hens fed on a high-energy diet (2800 ME kcal/kg) were significantly (P≤0.01) increased in FBW and body weight gain than those fed on a low-energy diet (2600 ME 2600 kcal/kg) and they added that hens consumed more feed in response to feeding on the diet containing lower ME content (2600 kcal /kg) than those fed on the diet containing higher ME content (2800 kcal/kg) In harmony with our result, Omara et al (2009), reported that body weight gain for Lohmann Brown hens, were significantly increased as a result of feeding the energy-sufficient diets, than the birds fed diets with lower energy contents. This may be due to the fact low dietary ME levels reduced available energy for fat deposition resulting in decreasing body weight gain.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Also the daily protein intake (P≤0.05) and daily energy intake (P<0.01) of the former were significantly higher than those fed the H ME diet. Our results are in accordance with those of Nofal et al (2018), who demonstrated that hens fed on a high-energy diet (2800 ME kcal/kg) were significantly (P≤0.01) increased in FBW and body weight gain than those fed on a low-energy diet (2600 ME 2600 kcal/kg) and they added that hens consumed more feed in response to feeding on the diet containing lower ME content (2600 kcal /kg) than those fed on the diet containing higher ME content (2800 kcal/kg) In harmony with our result, Omara et al (2009), reported that body weight gain for Lohmann Brown hens, were significantly increased as a result of feeding the energy-sufficient diets, than the birds fed diets with lower energy contents. This may be due to the fact low dietary ME levels reduced available energy for fat deposition resulting in decreasing body weight gain.…”
Section: Resultssupporting
confidence: 93%
“…However plasma cholesterol was significantly increased in response to feeding on H ME diet compared with those received the low-energy diet. These results consistent with the result of Nofal et al (2018), who indicated that feeding H ME -diet (2800 kcal/kg diet) to laying diets resulted in increasing cholesterol in blood plasma compared with the L ME -diets (2600 kcal/kg diet) but plasma levels of albumin, glucose and activity of AST were not affected.…”
Section: Blood Parameterssupporting
confidence: 91%
“…Our results are in line with our previous research (Alderey and El-Weshahy 2019), who found that energy levels had no effect on the characteristics mentioned, with the exception of cholesterol, which increased as diet energy increased, while, AST decreased. Also, Nofal et al (2018) found that feeding energy-diets (2800 kcal/kg diet) to laying diets increased blood plasma cholesterol when compared to low-energy diets (2600 kcal/kg diet), but glucose and albumin levels were unaffected. A similar study (Xin et al, 2022) found no negative impact on serum biochemical levels from lowered CP diets.…”
Section: Blood Parametersmentioning
confidence: 97%
“…feed intake, protein intake and energy intake of Silver Montazah laying hens. Nofal et al (2018) showed that hens fed a low-energy diet (2600 kcal/kg) had significantly lower FBW and body weight gain than hens fed a diet containing 2800 ME Kcal/kg. As well as hens fed on the diet with higher energy content consumed little feed and FCR was improved compared to low-energy content.…”
Section: Table (2): Effect Of Dietary Energy Levels Protein Levels An...mentioning
confidence: 97%